ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIFITAS IMPLEMENTASI SISTEM INFORMASI AKADEMIK (SIA) UNIVERSITAS GADJAH MADA - , DZIKRINA FITRIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to analyze the factors that influence the effectiveness of Sistem Informasi Akademik (SIA) back-end implementation from operators or administrators perspective as users. The effectiveness were measured by factors of User Satisfaction and Net Benefit, so the analysis were conducted to prove the effect of the Attitude Towards SIA with System Quality, Information Quality, Service Quality, and then to prove partially effect of these three quality dimensions towards User Satisfaction and User Satisfaction towards Net Benefit. This research employed primary data collected using questionnaire from the previous researches. The population of this research were SIA UGMâs operators or administrators in 14 undergraduate faculties in UGM. The data analysis methods employed in this study was simple regression analysis and hypothesis testing using t-test. The hypothesis test result prove that the Attitude Toward SIA significantly affect the System Quality and Information Quality, but does not affect Service Quality